Formação de docentes em nível médio e o ensino de ciências: estudo de caso de um curso da região Oeste do Paraná - Neumann, Sofia (2015)
The discussion on the importance of teacher training has been represented in a practical raised by theorists who deal on the importance of teaching. This discussion covers, in addition to continuing education, the initial training, which can occur within the higher education of teacher training or in average level, in the normal course. The State School Humberto de Alencar Castelo Branco - High School and Normal Course, in the city of Santa Helena, Paraná, Brazil, offers Teacher Training Course of Early Childhood Education and Early Years of Elementary School in average level, in Normal modality, in order to prepare teachers for Early Childhood Education and Early Years. As for the training of these teachers, it is questionable whether these students are prepared to work in Early Years, especially in Science subject. In this sense, we propose the present investigation, seeking to clarify what are the moments of formation available throughout the course, which are the methods employed in these moments with the students and how they enable the training of students/teachers in formation for science teaching. The qualitative research was conducted through interviews with two coordinators of the course, two teachers of the subject Methodology Education for Science, 10 formed students and the applying of questionnaires to 36 trainees to undergraduate in 2013. The central objective of the research was to identify the concept of Science Education that students and educators built along its enrollment process. In this paper we present the steps of the research and the results obtained thereby addressing the methodology used for the development of research; a literature review on the organization of the education system and teacher training throughout the history of Brazil, and how the teaching of sciences in the Early Years was being organized along the Brazilian education; the documents that guide the pedagogical work of the Teacher Training Course at Average Level and the Basic Curriculum for Municipal Public School in Childhood Education and Elementary School (early years), which guides the pedagogical work of the Early Years educators in elementary school; and finally, the search results and their analysis. The survey found that the contents of the subject Methodology Education for Science in the Teacher Training Course are worked superficially, experiencing a superficial training where students don´t appropriate properly in the necessary methods and content for the exercise of teaching. The course has an insufficient workload and high turnover of teachers to work with this subject. Therefore, we believe that the course of Teacher Training should be reconsidered in relation to the structure of the classes of subjects Methodology Education in all training areas, also it is necessary to rethought the distribution of teacher educators to the subject Methodology Education for Science.